PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN EDMODO TERHADAP HASIL BELAJAR MATEMATIKA (LPPM IKIP PGRI Bali, 2019)
The study aims to know the effect of problem based learning model assisted edmodo and personality type on result of learning mathematic in the class VIII of SMP Negeri. This type of research is quasi experiment, which is using treatment by level design. The population is the students of class VIII SMP Negeri 2 Kuta Utara that consists 14 classes with as many students is 525 students. Samples were taken in two experimental classes and two control classes taken using the multistage random sampling technique, it was obtained by class VIII L (36 students) and VIII M (36 students) as experimental classes and VIII A (38 students) and VIII D (38 students) as control classes. Data obtained with personality type questionnaire and result of mathematics students test. The data was analyzed by using Anava Two Lines and t-scheffe as further testing. Based on the result of data analysis indicate that: 1) there is difference of mathematics learning result between students following by problem based learning model assisted edmodo with students following conventional learning model, with  2) there is interaction between the learning model and the student personality type on the mathematics learning outcomes of students, with  3) on students with extrovert personality type, there difference of mathematics learning result between students following by problem based learning model assisted edmodo with students following conventional learning model, with  4) on students with introvert personality type, there difference of mathematics learning result between students following by problem based learning model assisted edmodo with students following conventional learning model, with . So, it can be concluded that problem based learning model assisted edmodo and personality type take effect result of the learning mathematic to the student in the class VIII SMP Negeri 2 Kuta Utara.